Commodity Price Shocks and Financial Sector Fragility - Kinda, Tidiane (IMF Working Papers; Working Paper ;, 2016)
This paper investigates the impact of commodity price shocks on financial sector fragility. Using a large sample of 71 commodity exporters among emerging and developing economies, it shows that negative shocks to commodity prices tend to weaken the financial sector, with larger shocks having more pronounced impacts. More specifically, negative commodity price shocks are associated with higher non-performing loans, bank costs and banking crises, while they reduce bank profits, liquidity, and provisions to nonperforming loans. These adverse effects tend to occur in countries with poor quality of governance, weak fiscal space, as well as those that do not have a sovereign wealth fund, do not implement macro-prudential policies and do not have a diversified export base. These findings are robust to a battery of robustness checks.